KAJIAN TOTAL BAKTERI PROBIOTIK YOGHURT BERAS MERAH DENGAN BERBAGAI VARIASI SUKROSA SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BIOLOGI SMA KELAS XII - Salsabil, Putri; Zulfarina, Zulfarina; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to determine total probiotic bacteria of red rice yoghurt with various variations of sucrose and the design of student worksheet (LKPD) of senior high school grade XII. This research was carried out in the Biology Education Laboratory FKIP UNRI in April-mei 2019. This research was conducted in two stages, namely the experimental stage: study of total probiotic of red rice yoghurt and the design phase of LKPD: analysis of potential and development of student worksheet. The research used an experimental method with Completely Randomized Design (RAL) consisting of 10 treatments and 3 replications. The parameter in this study is Total Plate Count (TPC), pH value, Lactic acid. The best combination of treatment is found in sucrose 12% and skim milk. Whilw based on the analysis of potential results of the study can be used as a Student Worksheet (LKPD) material for biology grade XII in Senior High School.Key Words: Fermentation of Red Rice Yoghurt, Full Cream Milk. LKPD Design,Skim Milk, Sucrose.